How alliances form and conflict ensues - Lu Dong; Lingbo Huang; Jaimie W. Lien; Jie Zheng (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
In a social network in which friendly and rival bilateral links can be formed, how do alliances between decision-makers form, and what determines whether a conflict will arise? We study a network formation game between ex-ante symmetric players in the laboratory to examine the dynamics of alliance formation and conflict evolution. A peaceful equilibrium yields the greatest social welfare, while a successful bullying attack transfers the victimized player's resources evenly to the attackers at a cost. Consistently with the theoretical model predictions, peaceful and bullying outcomes are prevalent among the randomly re-matched experimental groups, based on the cost of attack. We further examine the dynamics leading to the final network and find that groups tend to coordinate quickly on a first target for attack, while the first attacker entails a non-negligible risk of successful counter-attack by initiating the coordination. These findings provide insights for understanding social dynamics in group coordination.
Keywords: C72; C92; D74; D85; F51; 330; network formation; conflict; alliance; bully; peace